CD30, CD15, CD50, and PAX5 Expressions as Diagnostic Markers for Hodgkin Lymphoma (HL) and Systemic Anaplastic Large Cell Lymphoma (sALCL) - Dody Ranuhardy; Evlina Suzanna; Resti M Sari; Dwi W Hadisantoso; Rizka Andalucia; Arif Abdillah (Interna Publishing, 2018)
Background: the expression of CD30, CD15, CD50, and PAX5 are used to help in confirming diagnosis of HL and sALCL; however data on the proportion of these markers have not been available. The study was aimed to identify the proportion of CD30, CD15, CD50 and PAX5 expressions and characteristics of patients with HL and sALCL at Dharmais National Cancer Center Hospital between 2005 and 2015. Methods: a retrospective observational study was conducted using data from medical records and histopathological results of HL and sALCL adult patients who sought treatment at the hospital between 2005 and 2015. Immunohistochemistry (IHC) examinations were performed and data on the proportion of positive CD30, CD15, CD50, and PAX5 expressions were analyzed descriptively. Results: a total of 45 patients were recruited in this study, with the majority (42 patients, 93.3%) were HL patients and only 6.7% were sALCL patients. The median age of HL patients was younger than sALCL patients; 35 (18-72 years old) versus 54 (49-61 years old). Moreover, the immunohistochemistry examination demonstrated that the positive CD15, CD30, CD50, and PAX5 expressions were found respectively in 37.5%, 88.9%, 31.2%, and 31.2% patients with HL; while in patients with sALCL, in spite of their small sample size, positive CD30, CD15, CD50 and PAX5 expressions were found in 100%; 66,7%; 50%; and 50%, respectively. Overall, CD15, CD50, and PAX5 positive expressions were found in 39.5%, 32.4%, and 32.4% patients who had HL and sALCL; while positive expression of CD30 was found in 89.5% of them. Conclusion: present study shows that almost 90% patients have positive CD30 expression;  while the positive expressions of CD15, CD50, and PAX5 are found in less than 40% patients. It indicates that CD30 is an important diagnostic marker for HL and sALCL and it may improve treatment strategy.